Isotopic study of geographic origins and diet of enslaved Africans buried in two Brazilian cemeteries. (June 2016) - Bastos, Murilo Q.R.; Santos, Ricardo V.; M. de Souza, Sheila M.F.; Rodrigues-Carvalho, Claudia; Tykot, Robert H.; Cook, Della C.; Santos, Roberto V.
Abstract: Brazil was the main destination of enslaved Africans during the eighteenth and nineteenth centuries in the New World. We have analyzed isotopes of carbon, nitrogen and strontium in the enamel and dentin of teeth derived from remains of 41 enslaved Africans excavated in Pretos Novos cemetery (Rio de Janeiro) and Sé de Salvador cathedral (Salvador) in order to investigate aspects related to the geographical origins and dietary habits in Africa in these two groups with differing histories. Strontium isotope results indicate a wide range of geographical origin for the analyzed individuals of both cemeteries, being significantly wider in Pretos Novos. Carbon and nitrogen isotopes results suggest that the diet of most individuals was based on plants. Only 26% probably had access to a significant amount of animal protein. The results also show that while some individuals were consuming C3 plants such as yams and manioc, others had a diet based more on C4 plants such as sorghum, millet and maize. Interpreted in conjunction with archaeological and historical evidence, the findings of this study, including the high variability of 87 Sr/ 86 Sr, δ 13 C and δ 15 N values, contribute to the process of reconstructing the dramatic history of slavery in Brazil and in the Americas. Highlights: The analyzed individuals came from geologically diversified regions in Sub-Saharan Africa. Dietary habits were predominantly plant based, around 25% probably consumed significant amount of animal protein. Stable carbon isotope analysis indicated that individuals came from different agricultural populations.